The Evolution and Growth of Radha Soami Satsang Beas - Nayyar, Raman, (Brill | Manohar Publishers & Distributors, 2018)
This volume presents a detailed study of the growth of Beas branch of Radha Soami Satsang which started from a wild grass strewn area of a few square yards and which has now been converted into a well planned self governed township under the leadership of its five spiritual masters - Baba Jaimal Singh, Baba Sawan Singh, Baba Jagat Singh, Baba Charan Singh and the present Master Baba Gurinder Singh. It also takes into account through extensive fieldwork the historical background, philosophy, national and international growth, administrative structure, social welfare activities and literary works undertaken by the Beas branch. It adds new dimensions to one's understanding of how a religious philosophy propagated by its masters could attract millions of followers from all over the world. The work is largely based on the information collected through the author's personal visits to Dera Beas and its other satsang centres, interviews of some Dera devotees besides Dera Library Archival records, Dera magazines, Government records and secondary sources. This volume also contains detailed maps, appendices and a glossary which adds immensely to the scholarly nature of the work.